1985
DOI: 10.1152/jn.1985.53.2.557
|View full text |Cite
|
Sign up to set email alerts
|

Use-dependent depression of IPSPs in rat hippocampal pyramidal cells in vitro

Abstract: We have used intracellular recording techniques to study the use-dependence of evoked inhibitory postsynaptic potentials (IPSPs) in rat CA1 hippocampal pyramidal cells. We determined reversal potentials and conductance changes associated with IPSPs and responses to directly applied gamma-aminobutyric acid (GABA). The IPSP depression could be seen after a single conditioning stimulus. This depression appeared to be due primarily to a 50% decrease in IPSP conductance (gIPSP). Trains of stimulating pulses (50 pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
1
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(127 citation statements)
references
References 0 publications
10
115
1
1
Order By: Relevance
“…The marked depression of both inhibitory components at comparatively low rates of stimulation corroborates and extends previous investigations on frequencydependent, depression of IPSI's (Curtis & Eccles, 1960;Ben-Ari et al 1979;McCarren & Alger, 1985). This attenuation occurs in a frequency range where no significant effects on EPSPs are detectable.…”
Section: Contribution Of Local Circuits To Frequency Dependence Of Ipspssupporting
confidence: 89%
See 3 more Smart Citations
“…The marked depression of both inhibitory components at comparatively low rates of stimulation corroborates and extends previous investigations on frequencydependent, depression of IPSI's (Curtis & Eccles, 1960;Ben-Ari et al 1979;McCarren & Alger, 1985). This attenuation occurs in a frequency range where no significant effects on EPSPs are detectable.…”
Section: Contribution Of Local Circuits To Frequency Dependence Of Ipspssupporting
confidence: 89%
“…The decline of IPSPs at higher frequencies of FREQU TENCY DEPENYDENCE OF NEOCORTICA L IVHIBITION 515 stimulation in hippocampal neurones in vitro is associated with changes in conductance and the ionic gradient (McCarrent & Alger, 1985) anid fadinlg of GABA responses has been attributed to shifts of the Cl-equilibrium potential (Segal & Barker, 1984;Huguenard & Alger., 1986). The concomitant extracellular K' changes reported (McCarren & Alger, 1985) may have also affected the inhibitory gradient.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the exact function of GABAergic inhibition in the integrative activity of the cortex remains unclear, its importance is underscored by studies showing that the pharmacological blockade of GABAA receptor lead to epileptiform activity (Schwartzkroin & Prince, 1980) and that deficiencies in the GABAergic inhibitory system may be involved in some forms of human epilepsy (Lloyds, Bossi, Morselli, Munari, Rougier & Loiseau, 1986). In addition, modification of inhibition may be involved in both short-term (Ben-Ari, Krnjevic & Reinhardt, 1979;XXTong & Wlatkins, 1982;McCarren &, Alger, 1985;Thompson & Gaehwiler, 1989) and long-term (Stelzer, Slater & ten Bruggencate, 1987; Miles & Wong, 1987) changes in neuronal activity following tetanic stimulation of afferent fibres to the hippocampus. Simulation studies (Traub, Miles & Wong, 1989), based on data obtained from the hippocampal slice preparation, showed that reverberating, synchronized activity appears in groups of hippocampal cells when inhibition is reduced.…”
Section: Introductionmentioning
confidence: 99%